Mobilization of immunoglobulin (Ig)-containing plasma cells in Harderian gland, cecal tonsil and trachea of broilers vaccinated with Newcastle Disease Vaccine - Md. Zahirul Islam Khan; M. Nasrin; M.N.H. Siddiqia; M.A. Masuma (ELSEVIER, 2013)
Immunohistochemical studies of Harderian gland, cecal tonsil and trachea of various groups of broiler chickens and the response of Baby Chick Ranikhet Disease Vaccines (BCRDV) on the mobilization of Igs-cells during postnatal development of organs was investigated in the Dept. of Anatomy and Histology, Bangladesh Agricultural University, Mymensingh. In this study twelve chickens were grouped into vaccinated broilers (D14 and D28) which had received vaccines first at D3 of age and a booster dose given at D13; and non-vaccinated broilers (D1) which had not been vaccinated. In this study, it was observed that the frequency and distribution of Igs-positive cells were higher at D14 and at D28 rather than D1. Among Igs-positive cells, the IgG-positive cells were significantly higher than IgM and IgA-positive cells in the Harderian gland of D14 and D28 groups of chickens, however, in dayold chickens, the frequency of IgM-positive cells in this gland were greater. In the cecal tonsil, the frequency and distribution of IgG-positive cells were significantly higher than IgA- and IgM-positive cells both at D14 and D28 ages of chicken. On the other hand, in day-old chickens, the frequency and distribution of IgA-positive cells were insignificantly greater, followed by IgM and IgG-positive cells. In the trachea, few immunoglobulin-containing plasma cells were distributed in the subepithelial layer. IgM-positive cells were higher followed by IgG and IgA-positive cells in the trachea in D14 and D28 groups of chickens. In the same organ, IgG-positive plasma cells were greater than IgA and IgM-positive cells at one-day old. When the data for Harderian gland, cecal tonsil and trachea were compared statistically, it was observed that Igs-positive cells were statistically more common in cecal tonsils in day old chickens, and with the advancement of age, Igs-positive cells were found more in the Harderian gland. In conclusion, with the advancement of age in chickens the Harderian gland uptake is a function of the cecal tonsil due to its functional atrophy.